Las experiencias adversas en la infancia y sus secuelas psíquicas en la adultez - Lima Zambrano, Emely Fabiana; Ocampo Sánchez, Maria Del Cisne (Machala : Universidad Técnica de Machala, 2023)
Adverse childhood experiences comprise a set of events and circumstances with a stressful and traumatic potential, which negatively affects the well-being of children and adolescents before they turn 18 years of age. These types of experiences also influence the environment in which the subjects who have suffered these events grow up, causing irreparable consequences that mark the life of the infant. The present study has a mixed approach to the extent that quantitative and qualitative data are analyzed where the consequences and psychological injuries of adverse experiences during childhood are evaluated. In addition, it has a cross-sectional descriptive scope, a phenomenological design was applied, which analyzes the subjective aspect of those involved in the research. The objective of the case analysis is to explore the psychological consequences in adults who have gone through adverse experiences during childhood. A non-probabilistic convenience sampling was applied involving four people over 24 years of age who have had these experiences during childhood. Interviews were used as research instruments, through which valuable information was obtained about the adverse experiences experienced and their impact on their personality; The Adverse Experiences Test was also used, which is a questionnaire that allows assessing abuse and domestic dysfunction; In addition, the Derogatis 90 Symptom Check Questionnaire was used, which allows for the detection of symptoms of mental disorders and which can be self-administered, as well as the PAI Personality Test, which allows for the evaluation of clinical and personality variables. Prior to the application of the instruments, the informed consent was signed with the research subjects where guarantees that the data they provide is of absolute academic exclusivity. Once the request is accepted, data collection continues. Once the data had been specified, the categorization system was created, which consisted of: Adverse experiences in childhood, clinical symptoms and psychological consequences, and personality traits. The information collected in the interview and the Adverse Experiences Test indicates that the subjects investigated experienced physical, psychological and even sexual abuse, lived experiences of mothers treated with violence, who lived with people who were imprisoned and abused substances such as alcohol and drugs, these situations have left traces that interfere in their lives. Regarding the assessment of clinical symptoms and psychological sequelae, the Derogatis questionnaire was applied, which includes nine categories. The results indicate that two of the subjects investigated require treatment because they present severe pathology and another is at risk. In the PAI Personality Test, the results indicate that the prevalence is in paranoia and borderline traits, which are subscales of the clinical scales. Regarding the scales related to the treatment, it is evident that they present suicidal ideations. In conclusion, the adverse experiences that the investigated subjects lived left psychological injuries that last into adulthood and that marked their personality traits.
Los eventos adversos en la niñez comprenden un conjunto de sucesos y circunstancias con un potencial estresante y traumático, que afecta negativamente al bienestar de los niños y adolescentes antes de que cumplan los 18 años. Este tipo de experiencias también influyen en el medio en el que crecen los sujetos que han sufrido estos eventos, provocando consecuencias irreparables que marcan la vida del infante. El presente estudio tiene un enfoque mixto en la medida que se analizan datos cuantitativos y cualitativos donde se evalúan las secuelas y lesiones psíquicas ante las experiencias adversas durante la niñez. Además, tiene un alcance descriptivo de corte transversal, se aplicó un diseño fenomenológico el mismo que analiza el aspecto subjetivo de los involucrados en la investigación. El análisis de caso tiene como obejtivo explorar las secuelas psíquicas en adultos que han atravesado experiencias adversas durante la infancia. Se aplicó un muestreo no probabilístico por conveniencia donde intervinieron cuatro personas mayores de 24 años que han tenido estas experiencias durante la niñez. Como instrumentos de investigación se emplearon la entrevista a través de la cual se obtuvo información valiosa sobre las experiencias adversas vividas y su repercusión en su personalidad; también se utilizó el Test de experiencias adversas que es un cuestionario que permite valorar el abuso y la disfunción doméstica; además se utilizó el Cuestionario de comprobación de 90 síntomas de Derogatis que permite detectar síntomas de trastornos mentales y que puede ser autoadministrado, así como también el Test de Personalidad PAI que permite evaluar variables clínicas y de la personalidad. Previo al proceso de recolección de datos, se firmó el consentimiento informado con los sujetos participantes donde se garantiza que los datos que proporcionen son de absoluta exclusividad académica, una vez aceptada la petición se continuo con la recolección de datos. Concretados los datos se procedió a realizar el sistema de categorización la misma que consta de: Experiencias adversas en la infancia, Sintomatología clínica y secuelas psíquicas y Rasgos de personalidad. En la información recolectada en la entrevista y el Test de experiencias adversas indican que los individuos investigados experimentaron abuso físico, psicológicos e incluso sexual, fueron testigos de madres tratadas con violencia, vivían con personas que fueron encarceladas y abuso de sustancias como alcohol y drogas, estas situaciones han dejado huellas que interfieren en sus vidas. En lo que respecta a la valoración de la sintomatología clínica y secuelas psíquicas, se aplicó el cuestionario Derogatis que comprende nueve categorías, los resultados indican que dos de los sujetos investigados requieren tratamiento porque presentan patología severa y otra está en riesgo. En el Test de personalidad PAI, los resultados indican que las prevalencias están en paranoia y rasgos límites que son subescalas de las escalas clínicas. En lo que respecta a las escalas relacionadas con el tratamiento, se evidencia que presentan ideaciones suicidas. En conclusión, las experiencias adversas que vivieron los sujetos investigados dejaron lesiones psíquicas que perduran en la adultez y que marcaron los rasgos de su personalidad.
Keywords: EXPERIENCIAS ADVERSAS; LESIONES PSIQUICAS; PERSONALIDAD; ADULTEZ Y ABUSO